Character Education Implementation of Environmental Care through Used Cooking Oil Utilization as Aromatherapy Candles Based on Project Based Learning - Dwi Prastyo; Ahmad Iqbal Hidayat; Rizky Habibur Rohman; Randy Saputra Mahmud; Noly Shofiyah; Fitria Eka Wulandari; Mahesa Maulana; Adi Jufriansah (International Conference on Education for All, 2023)
Education is a learning process conducted in schools as formal educational institutions to equip students with the skills and awareness needed for developing interests and talents while fostering independence. Education should be capable of generating ideas or works that contribute to the advancement of a nation, one of which is character education. The Research and Development Agency of the Ministry of Education and Culture has formulated 18 values encompassed within character education, one of which is environmental care. This objective can be achieved through project-based learning utilizing used cooking oil to create aromatherapy candles. The method employed in this endeavor is a practical approach, in which the author plays the role of a teacher or facilitator at the ICC Ladang Kosma, conducting project-based learning activities. The outcome of this initiative is that students at ICC Ladang Kosma acquire new knowledge and experiences regarding the positive and negative impacts of producing aromatherapy candles from used cooking oil, indirectly instilling character education among the students.